2006
DOI: 10.1097/01.mlr.0000237180.72275.82
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nurse, System and Quality Patient Care Outcomes in 8-Hour and 12-Hour Shifts

Abstract: Nurses working 12-hour shifts were more satisfied. There were no differences in quality outcomes. Flexibility and choice in shift length are important elements in a positive nurse work environment. This study represents an innovative attempt by a labor-management bargaining group to make an evidence-based decision. We encourage others to conduct similar studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 34 publications
4
71
2
3
Order By: Relevance
“…This is consistent with an earlier study in which statistically significant alterations in error rate were not seen until shifts reached 12.5 hours or longer. 7 This possibility is supported by several other studies [21][22][23] indicating neutral or positive relationships between shift length and performance for shifts of 8 and 12 hours in duration. As both rote and cognitively intense tasks are important in the PICU environment, the relationships between work hours and both task types need to be clarified further.…”
Section: Effect Of Work Hours On Task Completion Rate and Accuracysupporting
confidence: 79%
“…This is consistent with an earlier study in which statistically significant alterations in error rate were not seen until shifts reached 12.5 hours or longer. 7 This possibility is supported by several other studies [21][22][23] indicating neutral or positive relationships between shift length and performance for shifts of 8 and 12 hours in duration. As both rote and cognitively intense tasks are important in the PICU environment, the relationships between work hours and both task types need to be clarified further.…”
Section: Effect Of Work Hours On Task Completion Rate and Accuracysupporting
confidence: 79%
“…[48] This design was developed and the data collected by survey from adult general inpatient units. The authors identified study variables which were nursing outcomes, while the independent variable was identified based on the type of shift length (12 or 8-hour shifts).…”
Section: The Impact Of the 12-hour Shift On Fatiguementioning
confidence: 99%
“…There is a lack of guide that can provide policy-makers the optimal duty length (Stone et al, 2006). Many studies have illustrated that nurse duty hours' length has a mixed effect on patient safety and quality outcomes (Estabrooks et al, 2009;Philibert, Nasca, Brigham, & Shapiro, 2013;Stone et al, 2006). For instance, some studies have found that limiting duty hours leads to decreased continuity of care and increased workload, which in turn negatively affect patient safety and staff performance (Philibert et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a lack of guide that can provide policy-makers the optimal duty length (Stone et al, 2006). Many studies have illustrated that nurse duty hours' length has a mixed effect on patient safety and quality outcomes (Estabrooks et al, 2009;Philibert, Nasca, Brigham, & Shapiro, 2013;Stone et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%